Obtenção e caracterização de cocristais de secnidazol: uma abordagem promissora da engenharia de cristais no setor farmacêutico - Costa, Ana Georgina Oliveira Pontes (2024)
The pharmaceutical industry is one of the sectors of great worldwide relevance nowadays, for its prominence in the production of the medicines so necessary for the cure and prevention of several diseases and the co-crystallization arouses great interest in this sector. Control and understanding of the physical-chemical characteristics of the solid state of Active Pharmaceutical Ingredients (API) is an important part of the process of developing new drugs. To meet this demand, there is an urgent need for continuous research and optimization of production processes. Starting from this premise, crystal engineering applied to drugs aims to develop new structural designs through the strategic utilization of supramolecular synthons. This strategy that uses crystal engineering aims to improve the physicochemical properties of drugs, such as stability, solubility, bioavailability, dissolution, among others. In view of the above, in the present work, studies were conducted with Secnidazole (SNZ), a potent antimicrobial applied worldwide in the treatment of neglected diseases, aiming at the possibility of obtaining new designs of this drug, with the objective of overcoming the inherent stability challenges imposed by its hemi-hydrated form. Based on extensive research in the literature and after carrying out a meticulous screening of molecular interaction, through the method of slow evaporation crystallization and grinding between SNZ and a significant number of coformers, unprecedented co-crystals were synthesized with Fumaric Acid (FMA) and with 3,5-dinitrobenzoic Acid (DNZ), which were characterized by single-crystal X-ray diffraction employing synchrotron radiation and complemented with data from infrared spectroscopy and powder X-ray diffraction. Furthermore, multicomponent compounds of SNZ with other coformers were obtained, such as succinic acid, citric acid, oxalic acid, thymol, and salicylic acid, which were also characterized by powder X-ray diffraction. In conclusion, this study significantly advanced the understanding of cocrystal formation involving secnidazole through systematic investigation and characterization of new solid forms. Therefore, it constitutes a contribution of significant relevance and alternative with the possibility of positively impacting the health of patients using this API, since the investment of the pharmaceutical industry in the research, development and optimization of drugs applied worldwide in the treatment of neglected diseases remains limited.